Brief behavioural surveys in routine HIV sentinel surveillance: a new tool for monitoring the HIV epidemic in Viet Nam - Duong Cong Thanh; Nguyen Tran Hien; Nguyen Anh Tuan; Hoang Thi Thanh Ha; Pham Hong Thang; Nguyen Thi Thanh Ha; Le Anh Tuan; Tran Dai Quang; Tran Hong Tram; Nguyen Le Hai; Phan Thi Thu Huong; Vo Hai Son; et al. (World Health Organization Regional Office for the Western Pacific, 2015)
In this report we describe a new approach in HIV sentinel surveillance that was piloted in Viet Nam in 2009 and is currently being rolled out in all provinces. It comprises a brief behavioural questionnaire added to the HIV sentinel surveillance surveys conducted routinely among people who inject drugs, female sex workers and men who have sex with men. Timely reporting of data from this system has resulted in improvements to HIV prevention efforts for most at-risk populations.